Measuring Projectile Velocity using Shock Wave Pressure Sensors - Padhy, Sankarsan; Panigrahi, Susmita (Defence Science Journal, 2014)
This paper deals with development of velocity measurement methodology based on projectile shock wave pressure measurements. The measurement principle is based on the fact that, whenever a projectile moves with supersonic velocity, shock wave fronts are produced along the trajectory of the projectile. Measurement configuration has been developed for measuring the shock wave pressure associated with projectile in flight, and hence, projectile velocity has been calculated. This paper covers various aspects of shock waves, generation of N Waves, feasibility study for capturing shock wave using dynamic microphone. Finally, suitable piezo-electric sensor has been selected and deployed in the trials and shock wave signature has been captured. From shock wave pressure, the projectile velocity has been computed. Defence Science Journal, Vol. 64, No. 6, November 2014, pp.499-501, DOI:http://dx.doi.org/10.14429/dsj.64.8108